Diversity without Race: How University Internationalization Strategies Discuss International Students - Buckner, Elizabeth; Lumb, Punita; Jafarova, Zahra; Kang, Phoebe; Marroquin, Adriana; Zhang, You (Journal of International Students, 2021)
This article examines how a sample of 62 higher education institutions in Canada, the United States and the United Kingdom discuss international students in their official institutionalization strategies, focusing on how ideas of race and diversity are addressed. We find that institutional strategies connect international students to an abstract notion of diversity, using visual images to portray campus environments as inclusive of racial, ethnic and religious diversity. Yet, strategy documents rarely discuss race, racialization, or racism explicitly, despite the fact that most international students in all three countries are non-white. Moreover, racial injustice is externalized as a global issue and racial diversity is instrumentalized as a source of improving institutional reputation or diversity metrics. We argue that a first step to creating more inclusive and anti-racist campuses is to acknowledge international students’ racial identities and experiences with racism in official discourses and strategies.